Rediscovery of Mictopholis austeniana (Annadale, 1908) (Squamata : Agamidae) - Das, Indraneil; Das, Abhijit (The Herpetological Society of Japan, 2007)
The poorly-known agamid lizard, Mictopholis austeniana, hitherto known from the unique holotype collected nearly a century ago from “Hills near Harmatti” (in Arunachal Pradesh, Northeast India), is reported from two sites in Arunachal Pradesh. The colouration of a live specimen is described and the species illustrated in colour for the first time.